Metallocene supported core@LDH catalysts for slurry phase ethylene polymerisation - Buffet, J; Byles, C; Felton, R; Chen, C; O'Hare, D (Royal Society of Chemistry, 2016)
We report the synthesis of solid catalysts based on a zirconocene supported on either silica@AMO-LDH or zeolite@AMO-LDH for the slurry phase polymerisation of ethylene. The hybrid catalysts demonstrate synergistic effects in which the polymerisation activity is up to three times higher than the zirconocene supported on analogous single phase silica or zeolite supports.